The Solow-Swan theories: An empirical evidence in various Indonesian Provinces - Yahya Mahda Vikia (Universitas Ahmad Dahlan, 2023)
The digital ecosystem is a collection of integrated information technologies and entities. The development of the digital ecosystem in Indonesia has shown a positive trend and has significant impacts on the national economy. The penetration of Information and Communication Technology (ICT) has brought positive effects such as increased accessibility, business growth, and digital economic transformation. To assess the progress of this technology, the Solow-Swan approach is employed. This research aims to examine how investment, labor force, and technology, represented by the level of mobile phone usage and Base Transceiver Station (BTS) infrastructure, can influence the economy through Gross Regional Domestic Product (GRDP) in the 34 provinces of Indonesia. This paper aims to examine how investment, labor, and technology can affect the economy through the GRDP in 34 provinces in Indonesia. The data used is panel data from 2018 to 2021 for 34 provinces in Indonesia. The research results show that investment and technological progress have a significant positive impact. On the other hand, the labor force has no effect on the economy in 34 provinces in Indonesia. Overall, this research has not been able to validate the Solow-Swan theory in the context of 34 provinces in Indonesia for the 2018-2021 period.